2019
DOI: 10.1287/mnsc.2018.3159
|View full text |Cite
|
Sign up to set email alerts
|

Malleable Lies: Communication and Cooperation in a High Stakes TV Game Show

Abstract: We investigate the credibility of nonbinding preplay statements about cooperative behavior, using data from a high-stakes TV game show in which contestants play a variant on the classic Prisoner's Dilemma. We depart from the conventional binary approach of classifying statements as promises or not, and propose a more fine-grained two-by-two typology inspired by the idea that lying aversion leads defectors to prefer statements that are malleable to ex-post interpretation as truths. Our empirical analysis shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…In the context of the hidden action game that we use, several experiments highlight a particular feature of verbal messages -a voluntary, non-binding promise to cooperate -as a credible signal of trustworthiness and an enhancer of trust. 5 This finding is also supported by field evidence from a TV show The Golden Balls, a highstake prisoner's dilemma environment with a pre-play stage of natural face-to-face communication moderated by the host (Belot et al, 2010;Van den Assem et al, 2012;Turmunkh et al, 2019).…”
Section: Introductionmentioning
confidence: 79%
“…In the context of the hidden action game that we use, several experiments highlight a particular feature of verbal messages -a voluntary, non-binding promise to cooperate -as a credible signal of trustworthiness and an enhancer of trust. 5 This finding is also supported by field evidence from a TV show The Golden Balls, a highstake prisoner's dilemma environment with a pre-play stage of natural face-to-face communication moderated by the host (Belot et al, 2010;Van den Assem et al, 2012;Turmunkh et al, 2019).…”
Section: Introductionmentioning
confidence: 79%
“…1 Also, the two studies were not run simultaneously and rates of promise-making differed substantially between these groups, 2 making it likely that different pools of participants were compared. Another study found that unconditional and explicit statements were associated with higher cooperation rates in a TV show than conditional or implicit statements (Turmunkh et al, 2019). Yet the types of statements varied considerably and included wishes and desires (e.g., "I want us to do X"), which we would not count as promises.…”
Section: Discussionmentioning
confidence: 99%
“…Workers were offered a choice between (a) $0.05 and (b) $0.15 under the condition that they commit to paying back $0.05 (henceforth 15-5). Since there have been few systematic studies on the effect of different commitment formats on promise-keeping (Charness & Dufwenberg, 2010;Turmunkh, van den Assem, & van Dolder, 2019), we decided to address this question by implementing the following commitment variants in a between-subjects design: (1) promise (write): clicking on a radio button with the promise spelled out and typing "I promise" into a text box next to it (n = 147), (2) promise (click): only clicking on a radio button to promise (n = 146), and (3) ask: being asked to pay back a suggested amount of money with no mention of the word "promise" (n = 145). We also included (4) a noncommitment control condition, in which participants had the option to select (a) $0.05 or (b) $0.15 with the choice to pay back $0.05 or a different amount (n = 130).…”
Section: Methodsmentioning
confidence: 99%
“…Our paper adds to a long list of papers that have employed TV game shows for the study of decision making. Starting in the 1990s, researchers have used the behavior of contestants to investigate, for example, risky choice (Gertner, 1993;Metrick, 1995;Post et al, 2008), strategic reasoning (Bennett and Hickman, 1993;Berk, Hughson and Vandezande, 1996;Tenorio and Cason, 2002), discrimination (Levitt, 2004;Antonovics, Arcidiacono and Walsh, 2005;Belot, Bhaskar and van de Ven, 2012), cooperation (List, 2006;Oberholzer-Gee, Waldfogel and White, 2010;van den Assem, van Dolder and Thaler, 2012;Turmunkh, van den Assem and van Dolder, 2019), and bargaining (van Dolder et al,2 An exception is Datta Gupta, Poulsen and Villeval (2013), who use an experimental design that is close to our head-to-head game. In their data there is suggestive evidence that men compete more against women: out of the eight males who faced a female opponent, five chose to compete (62.5%), whereas out of the twelve males who faced a male opponent, only four chose to compete (33.3%).…”
Section: Introductionmentioning
confidence: 99%